THE PROCESS OF CHARACTER DEVELOPMENT IN EARLY CHILDREN: THE ROLE OF FAMILY, SCHOOL, AND COMMUNITY IN PERSPECTIVE - Hamsiah, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Unbeknownst to many, a child's character does not develop spontaneously; instead, it undergoes a process that involves specific phases, particularly during early development, especially for young children. Parental attention in shaping a child's character during this period is crucial. In forming the character of young children, the environment and the family role-play a significant influence. This research employs a qualitative descriptive method to explore this process. In this article, the researcher examines the process of forming the character of young children, focusing on three main elements: family, school, and community. The research findings indicate that the formation of the character of young children begins with the family, is further influenced by the school, and involves the role of the community, including play communities and talent development courses attended by young children. Nevertheless, the family remains the primary and foremost factor in the process of shaping a child's character, being the most minor and highly influential community for them.